Vides un zināšanu mijiedarbība onkoloģijas, ar traheostomu, pacientu aprūpē - Dulpe, Dace (Latvijas Universitāte, 2009)
Darba tēma ir “Vides un zināšanu mijiedarbība onkoloģijas, ar traheostomu, pacientu aprūpē”. Darba mērķis ir noskaidrot, kā vide ietekmē pacienta zināšanu un prasmju apguvi un to pielietošanu. Hipotēze – vides un zināšanu savstarpējā mijiedarbība var ietekmēt pacienta izglītošanas un aprūpes procesu. Darbā ir veikta literatūras analīze par cilvēka un vides savstarpējo mijiedarbību, stresu un motivāciju, veikts pētījums par vides un zināšanu mijiedarbību onkoloģijas, ar traheostomu, pacientu aprūpē un noskaidrots, ka pacientam piemērota un atbalstoša vide ir motivējoša, iegūt jaunas zināšanas un prasmes. Pētījuma laikā izvirzītā hipotēze apstiprinājās. Darbs sastāv no teorētiskās un pētniecības daļas, secinājumiem un pielikumiem. Darba rezultāti apkopoti, izanalizēti un attēloti 21 attēlos un 1 tabulā. Atslēgvārdi: vide, cilvēks (klients, pacients), stress, aprūpe, traheostoma, motivācija, apmācība.

The theme of the thesis: Interaction of environment and knowledge in oncology (with tracheotomy) patient care. The purpose of the thesis is to clarify how environment affects the process of acquiring new knowledge and skills and their application by the patient. Hypothesis: interaction of environment and knowledge can affect the educational process of a patient as well as patient care process. Analysis of literature on mutual interaction of a person and environment, stress and motivation is carried out in the thesis. Investigation on interaction of environment and knowledge in patient care for oncology (with tracheotomy) patients was made, and it was concluded that an appropriate and supporting environment is motivating for a patient, as it ensures acquiring of new knowledge and skills. In the course of investigation the hypothesis posed for the thesis was confirmed. The thesis consists of theoretical and exploratory part, as well as conclusions and appendixes. The results of the thesis have been summarized, analysed and depicted in 21 pictures and 1 chart. Keywords: environment, a person (a client, a patient), stress, care, tracheotomy, motivation, training.
Interaction of environment and knowledge in oncology (with tracheotomy) patients care
Keywords: Medicīna